On Analysis of Two-Way Contingency Tables with some Sampling Zero Cell Counts — Application to Human Reproduction Wastage according to Age — - Moussa, M. A. A. (Methods of Information in Medicine, 1980)
A systematic procedure is described for the analysis of I x J cross-classifications with some nonstructural zeros. This includes (1) use of pseudo-Bayes estimators to remove zeros (2) fitting the smoothed array to all possible configurations of the log-linear models (3) fitting the data to the quasi -independence model after omitting counts of some anomalous cells — on the basis of standardized residuals to detect the cause of deviation from the null independence model. As a guide, a risk function value is computed for each array of smoothed pseudo-Bayesian estimates.Real-life data (based on a sampling survey conducted on the population of female nurses in Kuwait) is used for illustration.
Keywords: Two-Way Contingency Tables; Pseudo-Bayes Estimators; Log-Linear Models; Sampling Zero Cell Counts; Quasi-Independence Model